La Inversión del Plan Ecuador en Seguridad Humana en el período 2008 al 2010 ha influido en el Fortalecimiento del Estado de Derechos en la Frontera Norte - Ayala Alarcón, Wilma Cecilia (2014)
The purpose of this research is to analyze the investment made in Plan Ecuador on Human Security in the period of 2008 to 2010 and how it has influenced the strengthening of the rule of law in the northern borderpf Ecuador. Therefore, the first chapter explores the advances that have been made in concept of Human Security; analyzing its evolution, from its emergence in the late twentieth century to the present, as well as the concept “rule of law” in the national context . The second chapter deals with thePlan Colombia’s problematic and its implications for Ecuador, moving then onto the importance of State Planning , the National Plan for Good Living and Plan Ecuador, emphazsizing the role of the Technical Secretariat of Plan Ecuador. The third chapter studies the situation of the provinces along the northern border , in order to highlight the particular situation in each area in order to determine its problems, as well as international cooperation activities origin, binational policies and SETECI’s role. Concluding, the hypothesis about the influence of the northern border investment and influence in strengthening the rule of law is confirmed, and some conclusions and recommendations are made.